Effect of the Interaction between Cavities and Flaws on Rock Mechanical Properties under Uniaxial Compression - Jianwang Li; Yu Zhou; Wei Sun; Zheng Sun (Advances in Materials Science and Engineering)
Cavities and flaws are common types of defects in rock specimens that have an important impact on the mechanical properties of rockmass. In this paper, cement mortar was used to prefabricate a rock-like specimen with two cavities and a single flaw, and the uniaxial compression test was carried out. The process of fracture evolution on the specimen surface was obtained by using photography technology. The evolution regularity of a fracture was monitored by utilizing acoustic emission (AE) technology during the process of the specimen failure. Moreover, three-dimensional (3D) tomograms of specimens after uniaxial compression were obtained by using computerized tomography (CT) scanning technology, investigating the development characteristics of microcracks and the distribution of the final macrofractures. The particle flow code in two dimensions (PFC2D) program was used to simulate the mechanical behavior of brittle rock combining with microcrack propagation. The calculated stress-strain curve, AE features, and fracture distribution of the specimen obtained from the PFC2D simulation were relatively consistent with the experimental results.